[PP.05.32] PROFOUND SYMPATHETIC NERVOUS SYSTEM ACTIVATION IN PATIENTS WTH RESISTANT HYPERTENSION. (September 2017) - Schlaich, M.; Hering, D.; Lambert, G.; Eikelis, N.; Philipps, S.; Lambert, E.; Sata, Y.; Esler, M.
Abstract : Objective: Sympathetic nervous system activation is established as a major contributor to the development of human arterial hypertension. The relevance of neural mechanisms in resistant hypertension has not yet been investigated in detail. We therefore aimed to assess the degree of regional sympathetic activation in patients with resistant hypertension. Design and method: We combined microneurographic assessment of central sympathetic outflow with renal noradrenaline kinetics using radiotracer dilution methodology to comprehensively assess the level and pattern of sympathetic activation in 49 patients with resistant hypertension (RH). Matching data from patients with essential hypertension (EH: n = 70) and normotensive control subjects (NT: n = 40) were analyzed for comparison. Results: Systolic and diastolic office blood pressure levels were highest in patients with RH. Both muscle sympathetic nerve activity and renal noradrenaline spillover (NT: 73 ± 52 vs EH: 132 ± 87 vs RH: 245 ± 187 ng/min; p < 0.01) were substantially elevated in RH. Compared to patients with essential hypertension the level of renal sympathetic nerve activity was almost doubled and more than three-fold higher in RH compared to normotensive control subjects. Conclusions: Our results provide unequivocal evidence for a profound activation of the sympathetic nervous system in patients with resistant hypertension. While these findings cannot necessarily establish a cause-effect relationship, they substantiate the notion that specific targeting of renal sympathetic nerves is an attractive and well-founded therapeutic approach to improve blood pressure control, particularly in patients with resistant hypertension.